Combined Use of Scoring Incisions and 2-octylcyanoacrylate Adhesive during Endonasal Septoplasty to Correct Cartilaginous Deviations. Issue 6 (November 2014) - Kim, Bo-Hyung; Kim, Jong-Yeup; Park, Jae Sung; Kang, Sung-Ho; Lim, Dae Jun; Yu, Myeong Sang
Background: Applying 2-octylcyanoacrylate (2-OCA) tissue adhesive onto scoring incisions may increase efficacy and prevent concavity recurrence after septal deviation treatment. The present study evaluates the utility of 2-OCA adhesive application during endonasal septoplasty. Methods: The postoperative outcomes were compared between two consecutive periods in a single surgical department. Between March 2011 and March 2012, 23 consecutive patients underwent septoplasty using scoring incisions without 2-OCA application (scoring alone group), and between April 2012 and April 2013, the scoring incision gaps were filled with 2-OCA in 27 patients (scoring + CA group). The patients were followed up for more than six months. Results: A straight septum was achieved in 37.0% of patients in the scoring alone group versus 58.3% in the scoring + CA group. The postoperative symptom score for nasal obstruction was significantly improved in both groups. Persistent septal swelling developed in three (12.5%) patients in the scoring + CA group. Neither group experienced major complications such as septal hematoma, abscess, or septal perforation. Conclusions: Application of 2-OCA adhesive onto scoring incisions appears to be a reliable and effective technique to correct deviated cartilage during endonasal septoplasty. However, the volume of 2-OCA applied onto the septum should be minimized to avoid potential foreign body reaction. A long-term follow-up study is warranted.